The Use Of Antonyms In The Poetry Of G.Dawletova - Jolımbetova Shiyrin Alisherovna (Euro Asian Journal Publishing, 2024)
The article examines the stylistic features of the poetry of poetess G. Dawletova. The article also analyzes. the use of antonyms in the poems of G.Dawletova. The conclusion was made on the basis of scientific literature and scientific souces.
Keywords: the language of fiction; antonym; the structure of dictionary; phraseological antonym